2012
DOI: 10.1890/11-0915.1
|View full text |Cite
|
Sign up to set email alerts
|

Making leaps in amphibian ecotoxicology: translating individual‐level effects of contaminants to population viability

Abstract: Abstract. Concern that environmental contaminants contribute to global amphibian population declines has prompted extensive experimental investigation, but individual-level experimental results have seldom been translated to population-level processes. We used our research on the effects of mercury (Hg) on American toads (Bufo americanus) as a model for bridging the gap between individual-level contaminant effects and amphibian population viability. We synthesized the results of previous field and laboratory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 82 publications
(112 reference statements)
3
46
0
Order By: Relevance
“…, Willson et al. ). Complex combinations of stressors (climate‐induced UV‐B radiation and pathogens) have been implicated in amphibian declines from empirical evidence as well (Kiesecker et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Willson et al. ). Complex combinations of stressors (climate‐induced UV‐B radiation and pathogens) have been implicated in amphibian declines from empirical evidence as well (Kiesecker et al.…”
Section: Discussionmentioning
confidence: 99%
“…Willson et al. () correctly point out that if toxicity occurs at metamorphic climax (after larval density‐dependent effects have taken place) large effects on the population occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show here that parental and larval exposure to metal contamination increases larval period length and reduces size at metamorphosis, both of which have the potential to decrease survival to adulthood and reduce lifetime reproductive output. Our results suggest that multistressor studies that examine interactive effects provide more environmental realism than single stressor studies-given the importance of the early months post-metamorphosis to juvenile survival in amphibian population models (sensu Taylor and Scott 1997;Salice et al 2011;Willson et al 2012), similar studies that examine the potential carryover effects of larval stressors to the terrestrial stage will be an important research direction in order to better predict the effects of environmental contaminants.…”
Section: Factormentioning
confidence: 92%
“…Additionally, Peterman et al (2011) and Semlitsch et al (2008) both reported higher levels of emigration away from harvested forests by resident amphibians. Our study was designed to prevent emigration using enclosures to examine in isolation the degree to which survival is affected by forest harvesting, especially given that terrestrial survival can have the greatest consequences for population persistence in amphibians (Biek et al, 2002;Willson et al, 2012). Increased mortality reduces the regenerative capacity of a population by eliminating current (via adult mortality) and future (via juvenile mortality) reproductive output.…”
Section: Discussionmentioning
confidence: 99%